2018
DOI: 10.1016/j.jeem.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The housing market impacts of wastewater injection induced seismicity risk

Abstract: Using data from Oklahoma County, an area severely affected by the increased seismicity associated with injection wells, we recover hedonic estimates of property value impacts from nearby shale oil and gas development that vary with earthquake risk exposure. Results suggest that the 2011 Oklahoma earthquake in Prague, OK, and generally, earthquakes happening in the county and the state have enhanced the perception of risks associated with wastewater injection but not shale gas production. This risk perception i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Historically considered unprofitable, fracking involves injecting water, sand, and chemicals into underground rock formations to produce oil and natural gas (Ferreira et al, 2018). Fracking has been widely used to produce crude oil in the United States for over 60 years, boosting U.S. energy production to unprecedented levels (Feyrer et al, 2017).…”
Section: Background and Empirical Predictionsmentioning
confidence: 99%
“…Historically considered unprofitable, fracking involves injecting water, sand, and chemicals into underground rock formations to produce oil and natural gas (Ferreira et al, 2018). Fracking has been widely used to produce crude oil in the United States for over 60 years, boosting U.S. energy production to unprecedented levels (Feyrer et al, 2017).…”
Section: Background and Empirical Predictionsmentioning
confidence: 99%
“…Their findings are consistent with those of previous studies on the manifestation of earthquake risk perceptions. Ferreira, Liu, and Brewer [51] examined the impact of seismic risk perception from wastewater injection, which is known to potentially induce earthquakes. They found that nearby earthquakes significantly increased the perceived risk, but their effect was limited to areas within 2 km of the injection well.…”
Section: Empirical Review Of Seismic Risk and Property Valuesmentioning
confidence: 99%
“…Increased seismic activity in the central and eastern United States has been associated with wastewater injection wells (Weingarten et al 2015). Using a hedonic valuation framework, Cheung et al (2018), Ferreira et al (2018, and Burnett & Mothorpe (2021) value seismicity risks associated with wastewater disposal injection wells in Oklahoma. These studies find evidence of declining housing prices owing to seismic risk.…”
Section: Water Scarcitymentioning
confidence: 99%